The administration of death notifications in murder cases: retelling the secondary victimization experiences of homicide co-victims - Reed, Mark D. (Criminal justice studies, 2022)
The death notification is regarded as one of the most defining events for families of sudden and unexpected death. Little is known how the death notification process impacts families who have lost a loved one to homicide. Using the focus group methodology, this study depicts the death notification process through the eyes of homicide co-victims and examines the patterned aspects of the notifiers’ association with co-victims as their relationships and contacts unfold across three critical phases of death notification: initiating contact with co-victims, delivering the notice, and providing assistance and referral to co-victims. Of particular interest is retelling personal accounts of secondary victimization that homicide co-victims experience during the death notification process and how they responded to such experiences. The paper concludes by discussing ways to improve death notification protocols and training guidelines and providing direction for future policy and practice.